Abiyoyo based on a South African Lullaby and folk story - Seeger, Pete 1919- (Reading rainbow book, 1994)
Banished from the town for making mischief, a little boy and his father are welcomed back when they find a way to make the dreaded giant Abiyoyo disappear.